The complete mitochondrial genome of Glycyphagus domesticus (Acari: Glycyphagidae) using next-generation sequencing: Insight into phylogeny of Acariformes. (September 2021) - Lan, Yangming; Feng, Shiqian; Stejskal, Vaclav; Wu, Yi; Aulicky, Radek; Cao, Yang; Li, Zhihong
Abstract: Glycyphagus domesticus (Acari: Glycyphagidae) is a pest mite with worldwide distribution. It damages stored products and produces allergens. Molecular diagnosis is important for the effective monitoring and control of stored-products and dust pest mites. The complete mitochondrial genome (mt genome) has become one of the most useful markers for molecular systematics, phylogenetics and diagnostics of stored-pest mites. In this study, next-generation sequencing was used to sequence the complete mt genome of G. domesticus . The complete mt genome was found to be 14, 333 bp in size, containing 13 protein coding genes, 2 ribosomal RNA (rRNA) genes and 22 transfer RNA (tRNA) genes. We constructed phylogenetic trees based on concatenated thirteen protein-coding genes and two rRNAs genes. Our overall results showed that G. domesticus was found in its own separate clade from the 29 other mite species, which is likely due to the fact that this represents the first assembled mt genome of a member of the family Glycyphagidae. Overall, our study enriches the growing mt genome database for the Acariformes and will promote further studies. Highlights: Got the mitochondrial genome by the next-generation sequencing. The first complete mitochondrial genome record of Glycyphagidae. The mitochondrial genome can do well in species identification and molecular phylogenetics.